Yahoo奇摩 網頁搜尋

  1. 1.a x+3>2 x>2-3 x>-1 1.b x-2<3 x<3+2 x<5 1.c 2(X+1)>4 2X+2>4 2X>2 X>1 1.d 7x-9>9x+7 7x-9x>7+9 -2x>16 x<-8 [because -2(-8)=16 but -2(-9)>16 -8>-9] 2. a...

    分類:科學及數學 > 數學 2007年07月23日

  2. 1. This statement is not correct because the internal energy of a substance is also affected by the substance's mass, material and state, but not only its temperature. Therefore, the temperature of X may not be higher than that of Y. 2. When the...

  3. 4. 20名學生加入了這個班並被分成4組,每組將會有16名學生。這班原有多少名學生﹖ 5. 森美原有$(18X-400)的零用錢。當她買了7x/4顆糖果後還剩下$6。已知每顆糖果的價錢是$2。 a) 以x來表示森美用了多少零用錢來買糖果。 b) 求x的值。 c) 求森美原有的零用錢。 6. 如果項是1024,求n...

    分類:科學及數學 > 數學 2007年03月03日

  4. 以下的algorithm用上以下的infinite series: pi/4 = 1 - 1/3 + 1/5 - 1/7 + ... 1. accept user input and store to a variable noOfTerms 2. if noOfTerms is greater than zero 2.1 initialize loop_count and pi_over_4 to zero 2.2 for loop_count equals 0 to noOfTerms (inclusively...

  5. 你放棄你果個解釋...我都唔浪費時間去解你聽..你聽住我果個先 兩個方法, 一係爆開佢, 一係就咁搵, 我唔會去爆 (2+x)^n the x term= nC1(2)^n-1(x) =n/2(2^n) the x^3 term=nC3(2^n-3)(x^3) =[n(n-1)(n-2)/6](2^n-3)(x^3) =n(n-1)(n-2)/48(2^n)(x^3) coefficient of x^3/the...

    分類:科學及數學 > 數學 2007年12月24日

  6. a1 = 1 a2= 1+2(1) = 3 a3= 1 + 2(1) + 2(2) =7 a(1) = 1 a(2) = 1 + 2(1) a(3) = 1 + 2(1) + 2(2) . . . a(n) =1+ 2(1) + 2(2) + ‧‧‧+ L 所以 L 是 2(n-1) a(n) = 1 + 2[ 1 + 2 + 3 + ...... + (n-1) ] 注意 : 括號中共有 (n-1) 項,不是 n 項,代入 (首項 + 末項)X項數/2時要小心 = 1 + 2{[1+(n-1)](n-1)/2} = 1 + (n-1) + (n-1)^2...

    分類:科學及數學 > 數學 2013年10月05日

  7. 6千元買入門級車,再買衫褲鞋襪&成副武裝都夠。 詳情去鎮洋單車個網睇下大約價錢,但千祈唔好去鎮洋買,因為大鋪一定貴。 行得大巴士的斜路就乜單車都上到(有前後變速的話) 除非你行D好極端既路,例如港島D巷仔,或 中環花園道上落斜(NOT...

    分類:體育 > 單車 2013年09月04日

  8. I think you should correct as below(in blanket): In recent years, playing video games have become a world trend. Most of children or people like playing video game in anyplace such as bus stations, MTR stations...

    分類:社會及文化 > 語言 2007年08月22日

  9. 1(a)(i) a(4) = 13 and a(5) = 21 (ii) L = 2(n - 1) a(n) = 1 + 2(1) + 2(2) + ... + 2(n - 1) = 1 + 2[1 + 2 + 3 + ... + (n - 1)] = 1 + 2n(n - 1)/2 = 1 + n(n - 1) (b)(i) L = 1 + n(n - 1) + 2 * (n - 1) = 1 + n^2 - n + 2n - 2 = n^2 + n - 1 (ii) Sum = n * a(n) + [2 + 4 + ... + 2(n - 1)] = n + n^3 - n^2 + n(n - 1) = n^3 (a) The no. of...

    分類:科學及數學 > 數學 2013年10月09日